Using acceleration residual spectrum from single two-axle vehicle at contact points to extract bridge frequencies. (1st September 2022) - He, Yi; Yang, Judy P.
Highlights: Using single two-axle vehicle's acceleration residual spectrum obtained by front and rear contact points is proposed to extract bridge frequencies. The contact-point responses concerning two suspension systems in a vehicle are newly derived in the frequency domain. Better resolution of bridge frequencies is achieved in comparison with the existing method. The first three bridge frequencies can be extracted distinctly under various practical conditions for a simply-supported bridge. Regardless of different bridge boundary conditions, the proposed method is able to extract the first three or four bridge frequencies clearly. Abstract: Using the acceleration residual spectrum obtained by the front and rear vehicle-bridge contact points in a two-axle vehicle to extract bridge frequencies is proposed in this study, in which the contact-point responses concerning two suspension systems with dampers are newly derived in the frequency domain. In the identification of bridge frequency, as the extracted bridge frequencies are more or less contaminated by the pavement roughness-related frequencies in the vehicle scanning method, such an adverse effect of pavement roughness is recently eliminated by using the residual response of several connected single-axle vehicles or two-run tests by one vehicle. Nevertheless, the on-site operation of several connected vehicles or tests of two runs is hard to maintain consistent and stable conditions in practice. As such, an efficient and effective residual method using a single two-axle vehicle with one-run test is proposed. The numerical results show the following: (1) For a simply-supported bridge, the first three bridge frequencies can be extracted distinctly subjected to various parametric conditions. (2) Better resolution of bridge frequencies is achieved in comparison with the existing method. (3) Regardless of different bridge boundary conditions, the proposed method is able to extract the first three or four bridge frequencies clearly.